Relational enablers of information sharing: evidence from Chinese food supply chains. Issue 5 (12th June 2017) - Fu, Shaoling; Han, Zhaojun; Huo, Baofeng
Abstract : Purpose: Facilitating supply chain visibility and traceability through effective information sharing is vital to improve the quality and safety of food products. However, we know little about the enablers of information sharing in food supply chains. Drawing upon resource dependence theory and social exchange theory, the purpose of this paper is to explore how farmers' dependence on companies influences their trust in and relationship commitment to those companies, and in turn facilitates effective information sharing with them. Design/methodology/approach: Data collected from 462 farmers in China were used to test the conceptual model and related hypotheses. Findings: The results show that dependence has a significant positive effect on trust and relationship commitment, but it has no direct significant effect on information sharing. In addition, trust has a significantly positive influence on relationship commitment, and both trust and relationship commitment have significantly positive effects on information sharing. These findings show that strengthening farmers' dependence on companies can cultivate farmers' trust and relationship commitment, thereby encouraging them to share information with the companies. Originality/value: Theoretically, this study contributes to the supply chain information sharing and relationship management literature. Practically, it shows how companies can effectively monitor production processes and improve food quality and safety through information sharing and relationship management.